Breaking Free of the Branch : Designing Alternative Delivery Channel Projects for Microfinance Banks in Africa - Gutin, John (World Bank, Washington, DC, 2015)
Nearly 80 percent of adults in Sub-Saharan Africa do not have an account with a formal financial institution. Despite recent well-publicized successes in increasing financial inclusion in a small number of African markets, such as Kenya, hundreds of millions of African adults still lack access to affordable financial services. In response to this need, International Finance Corporation (IFC) and The MasterCard Foundation partnered to introduce alternative delivery channels in IFC’s key microfinance partners in Africa. Although the partnership is still at an early stage, this smart lesson distills some general lessons from two of the first alternative delivery channel engagements. These lessons may be useful for other IFC teams in structuring such projects with microfinance clients.